Development and application of novel proteomics methods in proteomics research - Hao, Piliang (2015)
The sensitivity, throughput and accuracy of proteomics have improved considerably in the past years due to the development of novel technologies. However, characterization of protein post-translational modifications remains challenging, especially those less studied ones. Protein deamidation is reported to be involved in aging and many diseases, but so far is less studied due to technical challenges. The existing challenges for accurately identifying and quantifying protein deamidation sites in proteomics include tremendous false positive identifications of deamidated peptides from database searches, substantial interference of artificial deamidation from sample preparation, difficulties in differentiating and quantifying the isomeric n-Asp and isoAsp deamidation products in proteome scale, and inability of validating quantification of deamidated peptides by either ELISA or multiple reaction monitoring. In this thesis, novel proteomic methods were developed to overcome these challenges and facilitate the large-scale characterization of protein deamidation. The accurate and reliable characterization of endogenous protein deamidation becomes feasible with both false positive identifications and artificial deamidation minimized while using our new data analysis strategy and sample preparation protocols. High-resolution parallel reaction monitoring enables the accurate validation of deamidated peptides in unfractionated individual samples. In addition to the validation of these methods using both model proteins and complex tissue samples, we also applied them to the study of protein deamidation in human carotid atherosclerotic plaques from aged patients for predicting secondary cerebrovascular events. The biomarker candidates of deamidated peptides and proteins obtained from label-free quantification on pool samples were validated in 38 individual plaques using parallel reaction monitoring for their applicability as biomarkers. None of them reached the criterion as a clinically usable biomarker possibly due to the small sample size and high individual variation. However, these newly developed technologies open a door for scientists who are interested in understanding the role of protein deamidation in aging and many diseases.